2018
DOI: 10.5513/jcea01/19.4.2334
|View full text |Cite
|
Sign up to set email alerts
|

Body and milk quality traits of purebred Holstein and three-generation crossbred cows from Viking Red, Montbéliarde, and Holstein sires

Abstract: The objective of this study was to investigate the effects of 3-way rotational crossbreeding scheme of Holstein (HO) cows with Montbéliarde (MO), Viking Red (VR) and HO sires on body and milk quality traits. Cows were purebred HO; F1: (MO × HO; VR × HO); F2: [MO × (VR × HO); VR × (MO × HO)]; F3: {HO × [MO × (VR × HO)]}; HO × [VR x (MO × HO)]}. Data were collected on 745 cows kept in a commercial farm located in Northern Italy. Milk data were acquired from official milk recording and body condition score (BCS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
1
7
2
1
Order By: Relevance
“…Conversely, they contrast with studies that also reported lower milk yield [ 29 , 31 ], lower fat and lower protein contents [ 29 , 30 ] for primiparous F 1 compared to purebred HO ones. Regarding the functional performance, our results contrast with studies [ 29 , 31 , 32 ] who found lower SCS for F 1 compared to purebred HO primiparous. Finally, regarding the fertility performance, our results are in accordance with those of many studies [ 2 , 29 , 30 , 33 ] that reported shorter DO for F 1 primiparous compared to purebred HO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Conversely, they contrast with studies that also reported lower milk yield [ 29 , 31 ], lower fat and lower protein contents [ 29 , 30 ] for primiparous F 1 compared to purebred HO ones. Regarding the functional performance, our results contrast with studies [ 29 , 31 , 32 ] who found lower SCS for F 1 compared to purebred HO primiparous. Finally, regarding the fertility performance, our results are in accordance with those of many studies [ 2 , 29 , 30 , 33 ] that reported shorter DO for F 1 primiparous compared to purebred HO.…”
Section: Discussioncontrasting
confidence: 99%
“…To our knowledge, very few studies compared G 2 with F 1 for the performance characteristics we investigated [ 12 , 32 , 34 , 35 ], whether in their first parity or the next ones: they more commonly compare G 2 with purebred HO [ 11 , 27 ]. Our results report lower milk, fat and protein yields for G 2 crosses compared to purebred HO in their first parity, and shorter DO, which is in accordance with those studies.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a 9-fold increase in crossbred cows over the last decade in the United States (Hazel et al, 2017b), and they now account for 8 and 12% of the overall cattle population in Sweden and Denmark, respectively (Clasen et al, 2019). Most of the previous studies on crossbreeding in dairy cattle have focused on fertility (Malchiodi et al, 2014a;Hazel et al, 2017a), survivability (Hazel et al, 2014), body traits (Blöttner et al, 2011;Saha et al, 2018), and milk yield and quality (Hazel et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, los fenotipos reportados de las vacas del concurso, solo implicaron a la raza Holstein y a su cruza con Montbéliarde. De esta última raza se reportan promedios de proteína y grasa superiores a las Holstein en promedio (Koç, 2011;Saha et al, 2018); en las razas Holstein se reportan de 3.6 a 3.7 % en grasa y 3.27 a 3.3 % en proteína (Ávila et al, 2014); mientras que en la raza montbéliarde oscilan entre 3.5% en grasa y 3.9% en proteína (Maciuc et al, 2010;Montbeliarde UK, 2015), y esto es similar con las cruzas de Holstein x Montbéliarde (Malchiodi et al, 2011;Saha et al, 2018).…”
Section: Resultados Y Discusiónunclassified